RELATIONSHIP BETWEEN COGNITIVE RESERVE, MOTOR RESERVE AND THALAMUS VOLUMETRY IN OLDER ADULTS - Šneidere-Šustiņa, Anete; Šneidere, Kristīne; Dowell, Nicholas G.; Stepens, Ainārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
With the increasing worldwide population, an ongoing escalation in mild cognitive impairment and dementia is predicted. Motor reserve – the cumulative physical activity experience gained throughout  life, as well as cognitive reserve – the brain’s ability to overcome a pathology, such as neurodegenerative disorders, - has been identified as protective factors in cognitive decline. Thus, this study aimed to investigate the relationship between cognitive reserve, motor reserve, and brain volumetry in older adults. 44 older adults (M = 70, SD = 5.18, 77.3% female) with no self-reported significant neurological, ongoing oncological etc. disorders that might limit their participation in the study were involved in the study. All participants underwent a thorough life-style and psychological assessment, as well as structural brain MRI analysis. Overall, our study indicated the significance of a combination of lifestyle factors in predicting thalamic volume. The results of this study indicate that life-long participation in physical, intellectual, and social activities could be beneficial for preserving the volume of thalamus, which is among the first to decline due to aging.